Roles and Mechanisms of Regulated Necrosis in Corneal Diseases: Progress and Perspectives. (23rd May 2022) - Lin, Wanying; Chen, Minting; Cissé, Yacouba; Chen, Xiaofeng; Bai, Lang
Abstract : Regulated necrosis is defined as cell death characterized by loss of the cell membrane integrity and release of the cytoplasmic content. It contributes to the development and progression of some diseases, including ischemic stroke injury, liver diseases, hypertension, and cancer. Various forms of regulated necrosis, particularly pyroptosis, necroptosis, and ferroptosis, have been implicated in the pathogenesis of corneal disease. Regulated necrosis of corneal cells enhances inflammatory reactions in the adjacent corneal tissues, leading to recurrence and aggravation of corneal disease. In this review, we summarize the molecular mechanisms of pyroptosis, necroptosis, and ferroptosis in corneal diseases and discuss the roles of regulated necrosis in inflammation regulation, tissue repair, and corneal disease outcomes.